Litter and nutrient deposition in semi-arid ecosystem of Brazil (Caatinga) under silvicultural systems - Lucena, Marcelo Silva de; Alves, Allyson Rocha; Bakke, Ivonete Alves (Instituto de Ecología, A.C., 2019)
This study aimed to investigate the effect of silvicultural systems and of the uses of the soil on the accumulation of the litter, its relation with the recycling and the nutrient supply to the soil, in two areas of Caatinga, in the semi-arid region of Brazil. The first is in the Seridó ecological station; the second is on Pedro Cândido farm. The accumulated litter was collected in the rainy and dry periods with the aid of a litter trap of 0.25 m2, with 16 replicates in each area (4 replicates by silvicultural system). The litter was separated into the fractions of branches, leaves + reproductive structure and miscellaneous, and the values obtained for each fraction were submitted to analysis of variance, according to a randomized block design. For the chemical analysis of litter, samples composed by the four replicates of each fraction referring to each silvicultural system were analyzed, in both evaluated periods. In both periods, in the Seridó ecological station there were 1570 kg ha-1 and 1890 kg ha-1 of litter and 44.18 kg ha-1 and 59.05 kg ha-1 of nutrients returned to soil, respectively. In the Pedro Cândido farm, in both periods, there were 2320 kg ha-1 and 2290 kg ha-1 of litter and 55.86 kg ha-1 and 61.98 kg ha-1 of nutrients recycled to the soil, respectively. The largest accumulation of litter in the Pedro Cândido farm occurred due to the greater amount of branches, but this did not result in a better supply of nutrients. After 27 years of interventions, there was no influence of silvicultural systems on the fractions and amount of nutrients.